Fertility, pregnancy and neonatal outcomes of patients with adenomyosis: a systematic review and meta-analysis. Issue 1 (January 2021) - Nirgianakis, Konstantinos; Kalaitzopoulos, Dimitrios R.; Schwartz, Alexandra S. Kohl; Spaanderman, Marc; Kramer, Boris W.; Mueller, Michael D.; Mueller, Martin
Abstract: This study aimed to investigate the association of adenomyosis with fertility, pregnancy and neonatal outcomes. An electronic search was conducted using the MEDLINE, PubMed and Cochrane databases up to April 2020. Seventeen observational studies were included. Adenomyosis was significantly associated with a lower clinical pregnancy rate (odds ratio [OR] 0.69; 95% confidence interval [CI] 0.51–0.94) and higher miscarriage rate (OR 2.17; 95% CI 1.25–3.79) after treatment with assisted reproductive technology (ART). The lower clinical pregnancy rate was more significant in the subgroup of patients with short down-regulation protocols. Similar associations were recorded after age adjustment. Adenomyosis was also significantly associated with an increased risk of pre-eclampsia, preterm delivery, Caesarean section, fetal malpresentation, small for gestational age infancy and post-partum haemorrhage, which was confirmed after correction for age and mode of conception. In conclusion, adenomyosis is associated with negative effects on fertility after ART. The potentially protective role of the ultra-long down-regulation protocols needs further evaluation in randomized controlled studies. Adenomyosis is also associated (independently of the mode of conception) with adverse pregnancy and neonatal outcomes. Proper counselling prior to ART and close monitoring of pregnancy in patients with adenomyosis should be recommended.